Scalable vector graphics and web map publishing - Da Silva Ramos, Cristhiane; Cartwright, W.; Doin De Almeida, Rosângela [UNESP] (Springer Nature, 2007)
The product development discussed in this chapter aimed at developing a methodology for publishing Brazilian local school atlas on the Web that would be easy-to-use and inexpensive. A low cost solution for publishing atlases on the Web is considered necessary in Brazil because most local school atlases are developed by academic teams with research funds which are, most of the time, very limited. Open Standard Technologies were chosen as the main tool for developing such products because they can be used at no cost. The use of SVG and JavaScript to produce online school atlases proved to be very effective. The final product, tested in Brazil with primary school teachers, received a very positive feedback. The experience described here illustrates that it is possible to develop a digital local atlas for education at greatly reduced costs. It is also possible that, in the future, Brazilian public universities can use their practical knowledge, developed through many years of work with paper atlases, to publish their products directly via the Internet, using the SVG Atlas Templates developed as part of this research. Nevertheless, it is believed that the main outcome of this project will be the 'digital inclusion', not only of public school children, but also of Brazilian children's atlas developers. © 2007 Springer-Verlag Berlin Heidelberg.